The Effect of Diet and Natural Agents on Oral, Periodontal Health and Dentistry - Isola, Gaetano (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Oral, periodontal diseases, chewing disorders, and many destructive inflammatory diseases of the supporting tissues of the teeth are caused by an imbalance between the host defense and environmental factors like bacteria, smoking, and poor nutrition. For these reasons, the focus should not only be on plaque control and removal of bacteria but also on improving host resistance through smoking abstention, stress reduction, and a healthy diet. The importance of micronutrients has been extensively reviewed, and it was concluded that prevention and treatment of periodontitis daily nutrition should include sufficient antioxidants, probiotics, natural agents, vitamin D, and calcium. Regarding antioxidants, vitamin C has attracted the attention of periodontal researchers. To date, there is limited available research investigating the effect of diet supplementation on the oral and periodontal condition.